(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The present study investigated the effects of Andaliman fruit extract on tumor necrosis factor-alpha (TNF-α) and transient receptor potential ankyrin-1 (TRPA-1) levels in type 2 diabetes mellitus (T2DM) mouse models induced with streptozocin (STZ) and a high-fat diet (HFD). Materials and Methods: In this research, mice were allocated into six distinct groups: normal, negative control (HFD and STZ), positive control (metformin, HFD, and STZ), and three treatment groups (HFD, STZ, and Andaliman extract at varying dosages of 100, 300, and 500 mg/kg, respectively). Body weight and blood glucose levels (BGLs) were recorded at weeks 1 (baseline), 8, 12, and 16. The levels of TNF-α and TRPA-1 were measured during the 16th week. Results: Phytochemical screening of the Andaliman extract revealed the presence of flavonoids, alkaloids, tannins, saponins, and glycosides. The one-way ANOVA revealed significantly elevated BGL at week 16 in the negative control group in comparison to the other groups (p < 0.05). The Kruskal-Wallis test followed by Bonferroni-corrected pairwise comparisons showed that the negative control had significantly higher TNF-α levels than the Andaliman-groups (z = 22.11, p < 0.01). TRPA-1 was significantly higher in the negative control group compared to the treatment groups (p < 0.05). Furthermore, Spearman’s rho analysis revealed a statistically significant positive association between BGL and both TNF-α and TRPA-1, as well as between TNF-α and TRPA. Conclusion: Andaliman extract potentially serves as a therapy for diabetic neuropathy in T2DM by lowering BGL and inhibiting the expression of TNF-α and TRPA-1. Adv. Vet. Anim. Res., 11(2): 284-290, June 2024 http://doi.org/10.5455/javar.2024.k774